INSOLVENT FOREIGN PRIVATE BANK: A STUDY ON MERGER AND LIQUIDATED BANKS - Haryati, Sri (Journal of Indonesian Economy and Business, 2011)
The purpose of this research was to apply the result of the previous studies onÂ predictive models of banks soundness in the year of 1999-2004 in private national banks,Â in which the result showed poor performance as was indicated by Z-score calculation ofÂ the discriminatory function of the cut-off position on less soundness and unsoundness level.The study also examined whether the financial ratios that must be published according toÂ SEBI No. 7/10/DPNP March 2005 are able to predict the level of banks soundness whenthey were implemented on the the discriminatory function.The research population was Indonesian Foreign Private Bank (BUSN). The secondaryÂ data used in this research were publications of financial statement during the five-yearperception time (2004-2008). The result of the research showed that the discriminatoryÂ function of previous research could apply to predict the soundness level of private foreignbanks in the period 2004-2008 and the financial ratios according to SEBI7/10/DPNPÂ publication in March 2005 were not enough to predict the soundness ratings ofÂ Indonesiaâs Foreign Private Banks.Keyworlds: soundness level of bank, Z-score, financial ratios